Encapsulation and backsheet adhesion metrology for photovoltaic modules. (26th September 2016) - Tracy, Jared; Bosco, Nick; Novoa, Fernando; Dauskardt, Reinhold
Abstract: Photovoltaic modules are designed to operate for decades in terrestrial environments. However, mechanical stress, moisture, and ultraviolet radiation eventually degrade protective materials in modules, particularly their adhesion properties, eventually leading to reduced solar cell performance. Despite the significance of interfacial adhesion to module durability, currently there is no reliable technique for characterizing module adhesion properties. We present a simple and reproducible metrology for characterizing adhesion in photovoltaic modules that is grounded in fundamental concepts of beam and fracture mechanics. Using width‐tapered cantilever beam fracture specimens, interfacial adhesion was evaluated on relevant interfaces of encapsulation and backsheet structures of new and 27‐year‐old historic modules. The adhesion energy, Gc [J/m 2 ], was calculated from the critical value of the strain energy release rate, G, using G  =  βP 2, where β (a mechanical and geometric parameter of the fracture specimen) and P (the experimentally measured critical load) are constants. Under some circumstances where testing may result in cracking of brittle layers in the test specimen, measurement of the delamination length in addition to the critical load was necessary to determine G . Relative to new module materials, backsheet adhesion was 95% and 98% lower for historic modules that were exposed (operated in the field) and unexposed (stored on‐site, but out of direct sunlight), respectively. Encapsulation adhesion was 87–94% lower in the exposed modules and 31% lower in the unexposed module. The metrology presented here can be used to improve module materials and assess long‐term reliability. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We present an adhesion metrology that can be used to assess long‐term reliability of photovoltaic modules. Using width‐tapered cantilever beam fracture specimens, interfacial adhesion was evaluated on encapsulation and backsheet structures of new and 27‐year‐old historic modules. Relative to new module materials, backsheet adhesion was 95% and 98% lower for historic modules that were exposed (operated in the field) and unexposed (stored on‐site, but out of direct sunlight), respectively. Encapsulation adhesion was 87–94% lower in the exposed modules and 31% lower in the unexposed module.